2014
DOI: 10.1007/s00127-014-0888-y
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported social anxiety symptoms and correlates in a clinical (CAP) and a community (Young-HUNT) adolescent sample

Abstract: Social anxiety symptoms were commonly reported by adolescents, in both clinical and community settings. These symptoms were associated with a broad spectrum of coexisting problems, which can be used to detect adolescents struggling with social anxiety. Adolescent, family, peer, school, and community interventions targeting these associated problems may contribute to prevent and alleviate social anxiety symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 39 publications
2
7
0
4
Order By: Relevance
“…Participants who reported that their family economic situation was worse than others had greater odds of being in the SP and SAD groups compared with those who reported having an equal family economic situation. This lends further support to a previously documented association between subjective perception of family economic situation and social anxiety (Wittchen et al, 1999;Ranøyen et al, 2014). Evaluation of the family's economic situation could be interpreted as a form of subjective socioeconomic status (SES), which has been shown to be associated with health outcomes, especially mental health outcomes (Quon and McGrath, 2014).…”
Section: Sociodemographic Characteristicssupporting
confidence: 76%
See 1 more Smart Citation
“…Participants who reported that their family economic situation was worse than others had greater odds of being in the SP and SAD groups compared with those who reported having an equal family economic situation. This lends further support to a previously documented association between subjective perception of family economic situation and social anxiety (Wittchen et al, 1999;Ranøyen et al, 2014). Evaluation of the family's economic situation could be interpreted as a form of subjective socioeconomic status (SES), which has been shown to be associated with health outcomes, especially mental health outcomes (Quon and McGrath, 2014).…”
Section: Sociodemographic Characteristicssupporting
confidence: 76%
“…and were presented with six response options: "no, never"; "yes, once"; "yes, 2-3 times"; "yes, 4-10 times"; "yes, 11-25 times"; and "yes, more than 25 times." In accordance with established practice (Strandheim et al, 2009;Ranøyen et al, 2014), we divided answers into three categories: no, 1-10 times, and 11 times or more. Smoking was measured with the item "Have you ever tried to smoke?"…”
Section: Questionnaire (N = 8199) Descriptive Variablesmentioning
confidence: 99%
“…La ansiedad, por ejemplo, puede dificultar el adecuado desarrollo del autoconcepto, llegando a suponer una falta de aceptación por parte de los demás, dificultades en el proceso de socialización y malestar (Gómez-Ortiz et al, 2016). Estos estados emocionales también pueden ser responsables de problemas académicos (Ranoyen, Jozefiak, Wallander, Lydersen, & Indredavik, 2014).…”
Section: Introductionunclassified
“…En este sentido, consecuencias desfavorables pueden ir asociadas a este tipo de estados emocionales. La ansiedad, uno de los más conocidos, puede dificultar el adecuado desarrollo del autoconcepto (Ranoyen, Jozefiak, Wallander, Lydersen, & Indredavik, 2014). Todo ello puede desencadenar desajustes psicosociales y enfermedades psiquiátricas.…”
Section: Introductionunclassified